Volume and Composition of Emboli in Neuroprotected Stenting of the Carotid Artery - Piñero, P. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Periprocedural microembolization is a major and permanent risk for patients treated by angioplasty and stent placement of high-grade carotid stenoses. Little is known however about the characteristics and significance of these embolized particles. Our aim was to assess the volume and composition of debris captured by filters during carotid angioplasty and stent placement (CAS) of severe internal carotid artery (ICA) stenoses. MATERIALS AND METHODS: Institutional review board approval and informed consent from all subjects were obtained. Two hundred one patients (mean age, 66.2 years; range, 35–82 years) with ≥70% stenosis of the ICA underwent filter-protected CAS. Ultrastructural and semiquantitative analysis of the volume of filters was obtained. Multifactorial statistical analysis was performed to determine factors related to debris volume and composition. RESULTS: Transient ischemic attack occurred in 6 patients (3%), and a major stroke, in 1 (0.5%). Debris was found in 117 filters (58.2%), with volume <1 λ (0.001 mL) in 71%. The number of balloon dilations, age older than 65 years, and calcified plaques in pre-CAS angiography were significantly associated with the presence of particulates inside the filters (P < .03, P < .004, and P < .05, respectively). CONCLUSIONS: Vessel wall and atheromatous plaques are the main source of microemboli during CAS. Embolization is mainly related to the number of balloon dilations during CAS. Planning a proper and individualized strategy for the procedure in each patient is essential to minimize the potential effects of manipulation during CAS.